Kapitał społeczny w gospodarce lokalnej - Brol, Ryszard (Social Capital in the Local Economy, 2008)
The local economy is a merger of related capitals: environmental capital, material capital, human capital, and social capital. The aim of this publication is to define the social capital as an economic category and on this basis to specify this concept, its source and the way to measure it. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 314-321